2021
DOI: 10.18203/2394-6040.ijcmph20210017
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of thumb sucking habit and its effect on developing malocclusion

Abstract: The persistence of thumb sucking might also be harmful as it might be associated with the development of complications seen on the thumb as paronychia and nail deformities and in the mouth level as malocclusions. In this review, we have looked up studies in the literature to identify the effect of thumb sucking on the development of malocclusion. Thumb sucking in children usually occurs as a primitive reflex that appears in early childhood with no apparent causative factors. Children usually develop this thumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…3 Another investigation conducted by Ahmed et al revealed similar results to our study. 5 Kharat et al concluded in his research that negative oral habits can lead to malocclusion. A total of 40% cases of malocclusion were found to be related to oral habits 15 , which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Another investigation conducted by Ahmed et al revealed similar results to our study. 5 Kharat et al concluded in his research that negative oral habits can lead to malocclusion. A total of 40% cases of malocclusion were found to be related to oral habits 15 , which is consistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Malocclusion occurs when these habits persist during and after the eruption of permanent dentition. 5 The frequency of oral habits and their consequences varies in different communities relying on factors such as type of parafunctional habit, its extent, frequency and intensity. 7 Bruxism is defined as the unintentional habitual grinding of teeth, which may cause attrition, periodontal problems and malocclusion.…”
Section: Introductionmentioning
confidence: 99%
“…4 The prevalence of sucking habits was 48.36% with the dummysucking as the dominant type and had broken their habits in the first few years of life while the more digit-suckers were still persistent at age 5 years reported by Farsi et al 2 The persistence of thumb sucking habit might leads to several harmful consequences like facial deformity caused by anterior open bite, delayed or abrupt tooth eruption, increased overbite, development of posterior crossbite and speech or phonological problems. 5 The management protocol of thumb sucking habit is wide spectrum approach that starts from reassurance of the child, application of non-invasive substances (bitter compounds) to thumb guard, habit reminder and habit breaking appliances. 6 Malocclusion of teeth & jaw is an important dental public health problem Its high morbidity potential has brought this problem into the focus of dental health professionals thus the different studies 20| P a g e Website: https://www.banglajol.info/index.php/UpDCJ were carried to figure out the association of thumb sucking habit.…”
Section: Introductionmentioning
confidence: 99%
“…Paediatricians can play a crucial role in recognizing the dangers of thumb sucking and the problems it can cause, as they often see infants and young children early in life [4]. Various interventions can be employed to help children discontinue thumb sucking, such as advice, removal of comforting items, orthodontic appliances, unpleasant taste application, or behaviour modification techniques [5] [6]. Dental professionals and paediatricians should educate parents and caregivers about the potential negative consequences of thumb sucking and implement appropriate interventions [6].…”
Section: Introductionmentioning
confidence: 99%